(3fXQjI GdfbhO aj Gdabg GdESdGej GdebGQf (B/s - (3Ndjd,QjGf Jhajbs ((3YeGf, GdCQOf (B:s (3OGQ GdaJM ddOQGSGJ hGdfTQ,s, 2014)
(3jJfGhd cJGH (B((3fXQjI GdfbhO aj Gdabg GdESdGej GdebGQf(B) (3hGdPj bGe HJCdjag GdOcJhQ QjGf Jhajb Ndjd aj MhGdj (B(478) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdCehGd aj Gdabg GdESdGej(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3GdfbhO fTCJgG hCfhGYgG hbhGYOgG hEUOGQgG, GdaUd GdKGfj (B: (3GdJcja Gdabgj ddfbhO hCMcGegG, GdaUd GdKGdK (B: (3GdQHG hGdUQa aj GdfbhO, GdaUd GdQGHY (B: (3GdJWHjbGJ GdeYGUQI aj GdfbhO (B... (3hZjQgG ef GdehVhYGJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B445-473.s
(3JLdjO SdhaGf(B.s
Keywords: (3GdGehGd (B((3abg GSdGej(B)s; (3GdfXGe GdeGdj aj GdESdGes